Influence of binder composition on the gel structure in alkali activated fly ash/slag pastes exposed to elevated temperatures. Issue 2 (1st February 2017) - Lee, N.K.; Koh, K.T.; An, G.H.; Ryu., G.S.
Abstract: The present study investigated the influence of binder composition on the gel structure in alkali-activated fly ash/slag (AFS) paste exposed to elevated temperatures, and correlates the strength gain behavior with the phase transformation of binder gels. XRD, solid-state 29 Si and 27 Al MAS NMR, MIP were conducted to characterize the thermally induced microstructural and chemical changes of the binder gel phases. The XRD patterns of AFS paste exposed to 800 °C showed the presence of the main phases akermanite (Ca2 MgSi2 O7 ), gehlenite (Ca2 Al[AlSiO7 ]), anorthite (CaAl2 Si2 O8 ), and minor quantity of nepheline ((Na, K)AlSiO4 ). The amount of crystalline phase formed after exposure to 800 °C is highly dependent on the Ca/Al ratio of the precursor, slag and fly ash. The pore structure of the AFS paste with a lower slag content after exposure to 800 °C became more porous, which is highly associated with that N-A-S-H, anorthite and nepheline formed by exposure to 800 °C are of significantly porous structure. The residual strength at 800 °C was highest at a lowest slag content (25%), which is likely due to the inherited high thermal stability of the highly cross-linked gel with Q 3 and Q 4 structures such as N-A-S-H, anorthite or nepheline, rather than the presence of C-(A)-S-H.